Distribution, sources and biogeochemistry of organic matter in a mangrove dominated estuarine system (Indian Sundarbans) during the pre-monsoon. (20th December 2015) - Ray, R.; Rixen, T.; Baum, A.; Malik, A.; Gleixner, G.; Jana, T.K.
Abstract: The sources and distribution of dissolved organic carbon (DOC), particulate organic carbon (POC) and dissolved inorganic carbon (DIC) in the Indian Sundarbans mangrove and Hooghly estuarine system were examined during the pre-monsoon (summer) 2014. DOC is the dominant form of organic matter (OM) in the studied estuarine waters and represents a mixture of mangrove and riverine sources. Microbial degradation of land derived OM results in a high pCO2 in the Hooghly estuarine waters while enrichment in δ 13 C-DIC ascribes to CO2 uptake by phytoplankton in the Sundarbans water. Higher δ 15 N in the particulate organic nitrogen (PON) of the mangrove and marine zone could be associated with enhanced phytoplankton production sustained by nitrate from mangrove derived OM decomposition and/or nitrate imported from the Bay of Bengal. Low organic carbon contents and elemental ratios (TN/TOC) indicate an intense mineralization and transformation of OM in the sediments, resulting insignificantly different OM compositions compared to those of the three major sources: land derived OM, mangrove leaf litter ( Avicennia marina ) and in situ phytoplankton production. Highlights: Sources of OM is studied for the first time in the Sundarbans applying elemental isotopes ( 13 C, 15 N) and their ratios. DOC is the dominant form of organic matter in the studied estuarine waters. DIC chemistry attributes to the heterotrophy and insitu production in the water system. POM is sourced from riverine, marine (phytoplankton) and mangroves (leaf litter). Intense mineralization and transformation of OM results in low OC percentages in the Sundarbans sediment.